Bioactivity, Molecular Docking, and Pharmacophore Modeling of Mycobacterium tuberculosis: A Study Targeting the Microarray Data of the Microbe - Soni, Nishant Kumar (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: Mycobacterium tuberculosis (TB) is the causative agent of tuberculosis (TB) and is responsible for more than eight million new infections worldwide and about two million deaths each year. New chemotherapeutics are required to treat the emerging threat of multidrug-resistant and extensively drug-resistant strains. Materials and Methods: Microarray data analysis techniques used to find novel gene target. In the present study, it was found that four novel genes named as MetZ (amino acid biosynthesis), aceAB (respiration system), relE (virulence activity), and kdaP (cell transport system) can be targeted that are inclusive of unique and important function in cell metabolism of organism. Discontinuing the function of these genes might kill the mycobacterium and prominently the specified relE gene, which plays a significant role in virulence effect, by inhibiting this gene, an individual with TB can be saved from TB disease if diagnosed and prognosis will be done at an early stage. Pharmacophore techniques are used in the present study to screen out lacs of molecule. Molecules downloaded from ZINC database are run through pharmacophore screening and docking procedure. Results: Finally, it was observed that top five (on the bases of binding energy) molecules from docking procedure gave improved result in ADME and toxicity analysis.